A Topic-Based Bibliometric Analysis of Two Decades of Research on the Application of Technology in Classroom Dialogue. (December 2020) - Hao, Tianyong; Chen, Xieling; Song, Yu
With growing interest in technology and its application within education, an increasing volume of research literature concerning the utilisation of technology in classroom dialogue has become available. To provide a comprehensive overview of the research area, this paper reports the results of topic-based bibliometric analysis of relevant articles published from 1999 to 2018. Trends in articles and citations, productive institutions, countries/regions and journals are identified. Vital research interests in the research area and how have they evolved over time have been specified and visualised. Interest in the application of technology in classroom dialogue has grown significantly during the past 20 years and will continue to expand. The USA is the top productive country in the field, and countries/regions and institutions that display a large number of international collaborations are likely to be influential. Topic analysis highlights the existing prominence of research in the areas of Dialogue, Settings, Collaboration and Information communications technology, as well as increasing interest in Learning achievement and Teacher professional development. Findings obtained in this study could potentially help promote the use of technology in classroom dialogue, and provide suggestions for scholars and project investigators in (re)allocating research resources.